Urban form as environmental noise indicators - Oliveira, Marta Isabela Fernandes (2012)
The urban form affects all systems and all species in an urban context and influences their behavior from the emission of noise, through its course until reaching the receiver, affecting the global climate. This paper seeks to address the problems of the urban environment as an area of interaction between urban forms and urban noise. This interaction is intended to be monitored by urban indicators, comparing the effects of noise propagation in an urban form model. The model of noise prediction (NMPB96), allows the development of studies about noise in facades (Ld, level of noise during the day), resulting in colors associated to noise categories. This study will allow the creation of different scenarios and to foresee, still in the draft phase, the facades exposed to a higher noise level. The effects of noise in facades can be, then, minimized in advance, by adjusting the layout of their typology. In order to validate the model and its results, we compared the values obtained at selected locations by modeling them. The validation of the theoretical curves was done in two phases. The first validation involved the measurement and the modeling of the selected real forms by comparing their receptor points. The second validation was done by calculating the average noise level on the facade of the modeled real forms, and then validated by comparing the calculation results of the indicators of form and behavior of the theoretical forms in order to correspond to its homonymous removed and measured in its real context. The study allowed the creation of different scenarios and anticipates, from its conception stage, the facades which have higher exposure to noise. Therefore, it is possible to minimize, in advance, the effects of noise on the facades, using the adjustment of the layout and configuration of the building form. The results showed that the physical characteristics of urban form influence sound propagation in a certain area. The urban parameters are important for determining sound of urban environment and, therefore, cannot be disregarded.